2018
DOI: 10.1016/j.ejps.2018.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the gastrointestinal tract of rats and the implications for oral drug delivery

Abstract: Pre-clinical research often uses rodents as animal models to guide the selection of appropriate oral drug and dose selection in humans. However, traditionally, such research fails to consider the gastrointestinal differences between the sexes of rats and the impact on oral drug delivery. This study aimed to identify and characterise the potential sex-related differences in the gastrointestinal environment of sacrificed male and female Wistar rats. Their gastrointestinal tracts were excised and segmented into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 39 publications
5
23
0
Order By: Relevance
“…An animal model study suggested stark physiological differences between male and female rats, indicating that the ‘sex of the gut’ could influence oral drug delivery. Compared with male rats, females displayed significantly higher relative P‐gp expression levels in the duodenum, jejunum and ileum . Second, physiological factors resulting in sex‐related pharmacokinetic differences include the generally lower bodyweight and organ size, higher percentage of body fat, lower glomerular filtration rate, and different gastric motility of females compared with males .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An animal model study suggested stark physiological differences between male and female rats, indicating that the ‘sex of the gut’ could influence oral drug delivery. Compared with male rats, females displayed significantly higher relative P‐gp expression levels in the duodenum, jejunum and ileum . Second, physiological factors resulting in sex‐related pharmacokinetic differences include the generally lower bodyweight and organ size, higher percentage of body fat, lower glomerular filtration rate, and different gastric motility of females compared with males .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with male rats, females displayed significantly higher relative P-gp expression levels in the duodenum, jejunum and ileum. 47 Second, physiological factors resulting in sex-related pharmacokinetic differences include the generally lower bodyweight and organ size, higher percentage of body fat, lower glomerular filtration rate, and different gastric motility of females compared with males. 48 Given that >90% of amisulpride is excreted unchanged via the kidney, the lower glomerular filtration rate in females may contribute to differences as well.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts have previously been made using Western blot analysis to investigate the distribution of P-gp in the rat intestinal tract, for instance; male Sprague-Dawley rats (Brady, 2002); fasted male Wistar rats (Valenzuela et al, 2004, Johnson et al, 2006, Wada et al, 2013; fed male and female Han-Wistar rats (MacLean et al, 2008); and fed male and female Wistar rats (Afonso-Pereira et al, 2018). The results of these studies, however, are inconsistent and further complicated by the differences in the reference proteins used to normalise transporter abundance.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, contradicting results have been reported regarding the segmental differences in Pgp expression along the small intestine. Several investigations have demonstrated that P-gp expression increases in the lower segments of the small intestine in rats (Hatton et al, 2015, Afonso-Pereira et al, 2018Mai et al, 2018) although others have reported that the highest expression can be determined towards the more proximal regions (Makhey et al, 1998, Yumoto et al, 1999, Stephens et al, 2002, Ho et al, 2003, Berggren et al, 2007. Assessing the methodologies used to determine P-gp in the literature, however, has revealed disparities in data collection regarding the reference protein, the strain of rat, the lack of consideration of potential sex differences and more notably, the influence of food on P-gp expression.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different animals used in preclinical research, rodents make up approximately 95% of all laboratory animals [2]. Specifically, rats are one of the most widely used small animal models for the assessment of new pharmaceutical entities during pre-clinical studies [3][4][5][6][7][8][9]. The oral route is the most preferred and convenient way to administer drugs which can either be formulated to act locally in the gastrointestinal (GI) tract or be absorbed to achieve a systemic effect [10].…”
Section: Introductionmentioning
confidence: 99%